Zespół Berdona oraz zespół suszonej śliwki i ich współistnienie - analiza przypadków - Płachno, Kamila; Spodaryk, Mikołaj; Pabisek-Miernik, Julita; Laskowska, Justyna; Wolnicki, Michał; Gabrowska, Elżbieta; Grela, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
This article presents the clinical analysis of patients with typical symptoms of Prune Belly Syndrome and Berdon Syndrome. We compare the clinical presentation of these syndromes with symptoms observed in a 11-month-old boy who displayed characteristics of both the syndromes mentioned.